2023
DOI: 10.1038/s41541-023-00685-z
|View full text |Cite
|
Sign up to set email alerts
|

The rVSV-EBOV vaccine provides limited cross-protection against Sudan virus in guinea pigs

Abstract: Recombinant vesicular stomatitis viruses (rVSVs) engineered to express heterologous viral glycoproteins have proven to be remarkably effective vaccines. Indeed, rVSV-EBOV, which expresses the Ebola virus (EBOV) glycoprotein, recently received clinical approval in the United States and Europe for its ability to prevent EBOV disease. Analogous rVSV vaccines expressing glycoproteins of different human-pathogenic filoviruses have also demonstrated efficacy in pre-clinical evaluations, yet these vaccines have not p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Animals immunized with Ly-VSV∆G/EBOVGP vaccine all had EBOV-specific ELISA titers > 1:6,400. Although those animals were not challenged with EBOV to assess the in vivo protective efficacy of the Ly-VSV∆G/EBOVGP vaccine, their antibody responses were consistent with a predicted protective response on the basis of findings from other studies, including studies using a similar EBOV guinea pig model ( 9 , 10 ). Instead, we used Ly-VSV∆G/EBOVGP–immunized animals as sham-vaccinated control animals in the lethal LASV challenge experiment to control for nonspecific immunity associated with the LST stabilizer formulation.…”
Section: The Studymentioning
confidence: 70%
See 1 more Smart Citation
“…Animals immunized with Ly-VSV∆G/EBOVGP vaccine all had EBOV-specific ELISA titers > 1:6,400. Although those animals were not challenged with EBOV to assess the in vivo protective efficacy of the Ly-VSV∆G/EBOVGP vaccine, their antibody responses were consistent with a predicted protective response on the basis of findings from other studies, including studies using a similar EBOV guinea pig model ( 9 , 10 ). Instead, we used Ly-VSV∆G/EBOVGP–immunized animals as sham-vaccinated control animals in the lethal LASV challenge experiment to control for nonspecific immunity associated with the LST stabilizer formulation.…”
Section: The Studymentioning
confidence: 70%
“…We evaluated vaccine-induced humoral immune responses in serum samples collected immediately before virus challenge (28 days postimmunization) by using LASV and EBOV glycoprotein-specific ELISAs, as previously described ( 8 , 9 ). Animals immunized with Ly-VSV∆G/EBOVGP vaccine all had EBOV-specific ELISA titers > 1:6,400.…”
Section: The Studymentioning
confidence: 99%
“…The pre-existing immunity against the vector also poses other obstacles to the clinical use of these candidates 28 . rVSV is an ideal vaccine platform that can easily incorporate other viral GPs and has been investigated extensively 16 , 29 31 . The most evident example is Merck’s certified ERVEBO, which is a replication-competent VSV that encodes the EBOV glycoprotein and shows the ability to induce a humoral immune response 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In a very recent article, Canadian and U.S. researchers tested the heterologous immunity hypothesis with two Ebolaviruses: Sudan and Zaire. In the guinea pig model, the authors demonstrated that 60% of animals vaccinated with a recombinant vesicular stomatitis virus (rVSV) engineered to express heterologous Zaire ebolavirus viral glycoprotein survived the challenge with Sudan ebolavirus [13]. These results indicated limited but relevant cross-protection in the rodent model.…”
Section: Among Ebolaviruses There Is Also Cross-protectionmentioning
confidence: 99%